New black-filled epoxy coatings for repairing surface of equipment of marine ships - Buketov, Andriy; Smetankin, Serhiy; Maruschak, Pavlo; Yurenin, Kyrylo; Sapronov, Oleksandr; Matvyeyev, Viktor; Menou, Abdellah (Transport, 2020)
The methods for ensuring long-term and safe operation of marine equipment due to comprehensive repair technologies that use epoxy oligomers and new compositions based on them are developed. The influence of temperature and UltraSonic Treatment (UST) on the rheological properties of the pure epoxy matrix and compositions based on it is explored. The compositions have different content of nanodispersed soot carbon black of brand PowCarbon 2419G (particle size of 24 ± 2 nm). It is established that when nanoparticle soot (q = 0.10…15.00 pts wt) is introduced into the composition of the epoxy matrix treated with ultrasound, the viscosity of the composition increases gradually. Based on the results obtained, temperature ranges are recommended, in which the viscosity of the studied compositions reaches optimal technological parameters for the effective impregnation of threads, tows and various fabrics, and which provide for the effective application of the composition to the working surfaces of marine equipment. Technical recommendations are given for applying the developed black-filled epoxy compositions to the working surfaces of parts, ship mechanisms and pipeline systems of marine vessels.First published online 28 January 2021